Efeitos do programa de condicionamento físico em portadores de NASH - Freitas, Vinicius de Lima (2017)
The prevalence of hepatic steatosis and non-alcoholic fatty liver disease (NAFLD) in the Brazilian population is not known, and there are few studies about this disease in the country. Lifestyle modification, including physical activity and exercise are first line recommendation for the tratment of patients with NAFLD. Aim: To evaluate the efficacy of the Supervised physical activity and exercise program on-site and distance-supervised with duration of 12-month for patients with non-alcoholic steatohepatitis (NASH). Methods: This is a prospective, longitudinal, open cohort study including consecutive patients who had a histological diagnosis of NASH in the last 12 months and who were followed up at the outpatient NAFLD clinic. Exclusion criteria were: patients with concomitant liver diseases who could lead to steatosis; history or active significant alcohol intake such as equal or greater than 210g / week for men and 140g / week for women; drugs known to be related to NAFLD; untreated hypo or hyperthyroidism; pevious bariatric surgery; obesity equal or greater than grade III; binge eating or other uncontrolled psychiatric disorder. The patients were studied withing a pre-stated protocol study including clinical and laboratory evaluation, as well as the Baecke questionnaire and the six minute walk test (6MWT), before and after participation in the physical conditioning program. Descriptive statistics, Student's tes and the Mann-Whitney test, were performed for parametric and non-parametric variables as apropriated. The significance level adopted was p-value >0.05. Results: From the 15 included patients, three of them did not complete the multidisciplinary program during the 12-month study period. Thus, the total sample analyzed was 11 patients, that is, 73.33% of included patients. The 5% goal for body weight loss was not reached, however low density lipoprotein (LDL) presented significant reduction at the end of the study (p = 0.0130). The distance-supervised program was chosen by all patients and walking was the main physical activity (66.67%), followed by soccer. The 6-min walk distance (6MWD) was sgnificantly higher at trhee and six month when compared with basal distance at the entry of the study. Conclusion: The distancesupervised physical activity and exercise program had high adherence and was effective in improving the functional capacity for patitients with NASH. On the other hand, there was partial improvement for biochemical and antropometric variables. Aditionally, this is a distance-supervised life-style modification program with low cost and high potential cost-benefit for patients with DHGNA and NASH attended on the National Health System.